Pemanfaatan Microsoft Access Dalam Pembuatan Database Perpustakaan Sekolah SMK Muhammadiyah Loa Janan - Jannatunnisa Jannatunnisa; Muhammad Taufiq Sumadi (BADAN PENERBIT STIEPARI PRESS, 2023)
Information management in school libraries plays a strategic role in supporting the effectiveness of learning activities. This community service aims to analyze the implementation of Microsoft Access as a solution in optimizing the efficiency of recording and managing library archives, especially at Muhammadiyah Loa Janan Vocational School. Microsoft Access integration was created to improve the quality of book borrowing records, speed up the information search process, and organize the continuity of borrowing. Library data management by utilizing Microsoft Access runs more effectively and efficiently.